''This Secret Town': British Intelligence, the Special Relationship, and the Vietnam War'. Issue 2 (15th March 2017) - Wolf, Nikita
ABSTRACT: This article seeks to revise our understanding of Cold War intelligence as a practice. The conventional view is that Britain's MI6 waged a battle in the shadows consisting of espionage and covert action. However, a number of MI6 officers operated as observers, conducting what we might call 'intelligence without espionage'. The dual identity of these officers raises important questions about how intelligence operated in the blurred space between traditional diplomacy and human espionage using agents. Using the case of MI6 officers in the British Consulate-General in Hanoi between 1965 and 1972, this article explores how a dual identity provided alternative means of acquiring intelligence within a highly secure state that exhibited remarkable paranoia about foreign spies. Furthermore, the United States lacked diplomatic representation in Hanoi and so the British Consulate provided a remarkable window for Western intelligence on the effect of 'Operation Rolling Thunder', Lyndon Johnson's escalating air campaign against North Vietnam. Both Johnson and Harold Wilson were avid readers of this material. Accordingly, in the context of the Cold War intelligence partnership between the UK and US, the consulate in Hanoi was an example of the 'inverse' special relationship, in which Britain enjoyed unique value.